Collagen fingerprinting traces the introduction of caprines to island Eastern Africa. Issue 7 (28th July 2021) - Culley, Courtney; Janzen, Anneke; Brown, Samantha; Prendergast, Mary E.; Wolfhagen, Jesse; Abderemane, Bourhane; Ali, Abdallah K.; Haji, Othman; Horton, Mark C.; Shipton, Ceri; Swift, Jillian; Tabibou, Tabibou A.; et al.
Abstract : The human colonization of eastern Africa's near- and offshore islands was accompanied by the translocation of several domestic, wild and commensal fauna, many of which had long-term impacts on local environments. To better understand the timing and nature of the introduction of domesticated caprines (sheep and goat) to these islands, this study applied collagen peptide fingerprinting (Zooarchaeology by Mass Spectrometry or ZooMS) to archaeological remains from eight Iron Age sites, dating between ca 300 and 1000 CE, in the Zanzibar, Mafia and Comoros archipelagos. Where previous zooarchaeological analyses had identified caprine remains at four of these sites, this study identified goat at seven sites and sheep at three, demonstrating that caprines were more widespread than previously known. The ZooMS results support an introduction of goats to island eastern Africa from at least the seventh century CE, while sheep in our sample arrived one–two centuries later. Goats may have been preferred because, as browsers, they were better adapted to the islands' environments. The results allow for a more accurate understanding of early caprine husbandry in the study region and provide a critical archaeological baseline for examining the potential long-term impacts of translocated fauna on island ecologies.